2013
DOI: 10.3800/pbr.8.102
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of the red-tide raphidophyte Heterosigma akashiwo on growth of juvenile Manila clams, Ruditapes philippinarum

Abstract: Abstract:We studied the effects of Heterosigma akashiwo, a harmful algal species, in the diet of juvenile Manila clams (Ruditapes philippinarum), because it often blooms in coastal waters where aquaculture of the clams is carried out. Weight of soft tissue of clams increased when they were fed H. akashiwo added at 8,000 cells mL 1 , with weight growth about 8% higher than that of clams fed only Chaetoceros neogracile. In addition, a significant increase in the body-mass index and glycogen content was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Furthermore, these authors demonstrated that the clearance rates differed among the three examined bivalves and the brown tide-forming alga A. lagunensis. Overall, our study and previous reports have demonstrated that bivalves can feed effectively on HAB species, including H. akashiwo [34,35]. Further research is required for the investigation of the clearance rates of H. akashiwo by filter feeders.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, these authors demonstrated that the clearance rates differed among the three examined bivalves and the brown tide-forming alga A. lagunensis. Overall, our study and previous reports have demonstrated that bivalves can feed effectively on HAB species, including H. akashiwo [34,35]. Further research is required for the investigation of the clearance rates of H. akashiwo by filter feeders.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, pigment deposition indicated digestion of H. akashiwo after ingestion (Figure S2). It has been reported that H. akashiwo can promote the growth of the Manila clam, Ruditapes philippinarum [34]. Interestingly, significant increases in the soft-tissue weight, body-mass index, and glycogen content of the clams were found when the clams were fed H. akashiwo compared to control (fed only Chaetoceros neogracile) [34].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the roundness index and weight of soft tissue of the no-diet groups were significantly lower than those of the groups given any diet ( Table 1 ). Unfortunately, we could not analyze the glycogen content in clams because whole clams were used for the metabolomics analysis, but several studies have indicated that glycogen content in clams is positively correlated with physiological condition 21 and the roundness index 15 . On the other hand, the metabolic pattern for glucogenic amino acids such as glycine, serine, threonine, and tryptophan in the no-diet groups differed from the other test groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Taga et al . reported the beneficial effects of the raphidophyte Heterosigma akashiwo , known as a harmful algal species, on the diet of juvenile R. philippinarum , and suggested the possibility that certain kinds of sugars, specifically the acidic sugars in phytoplankton, are one of the important factors determining the growth of juvenile clams 15 .…”
mentioning
confidence: 99%